Neighbourhoods Mobilise the Troops - Community Organising, Violence and Governmentality - Sabine Stövesand (Social Work & Society, 2007)
The article reflects on the difficult relation between community work against domestic violence and local crime prevention under the conditions of the neoliberal state that cuts down on social benefits and promotes self-help, active citizenship and self-responsibility instead while at the same time restoring the punishing state with its strict regime of law-and-order. The author describes a project Tarantula - she started herself while being a social worker in Hamburg, Germany. Tarantula was aimed at strengthening social networks and the neighbours' willingness to get involved in favour of affected women. Although conceptualized as an emancipatory approach referring to community organizing in the tradition of social movements it is questionable whether and how this can really work in the current situation. At present, the field of crime control is being reconfigured as a result of political and administrative decisions, which, for their part, are based on a new structure of social relations and cultural attitudes. The demolition of the 'welfare state' means the re-coding of the security policy that facilitates the development of interventionist techniques that govern and control individuals through their own ability to act.